Creatine supplementation supports the rehabilitation of adolescent fin swimmers in tendon overuse injury cases - Juhasz, I.; Plachy Kopkane, J.; Hajdu, P.; Szalay, G.; Kopper, B.; Tihanyi, J. (Journal of Sports Science & Medicine, 2018)
Our purpose was to investigate the effect of creatine (Cr) supplementation on regeneration periods in tendon overuse injury rehabilitation of adolescent fin swimmers. The participants of this study were injured adolescent competitive fin swimmers (n = 18). The subjects were randomly assigned the creatine (CR) or placebo (PL) groups with a double-blind research design. The subjects were given Cr supplementation or received the placebo as part of the conservative treatment of the tendinopathy. We measured the segmental lean mass (SLM;kg), the ankle plantar flexion peak torque (PFT;N·m), the pain intensity (NRS;values), prior to immobilization, after immobilization (R2) and after the 2nd (R4) and 4th (R6) weeks of the rehabilitation period of the injured limb. The creatine kinase (CK; U/L) enzyme levels were measured before immobilization, and then every 24 hours for four days. There was a significant decrease in SLM (CR by 5.6% vs. PL by 8.9%; p < 0.03) after two weeks of immobilization in both groups (p < 0.001). After four weeks rehabilitation the SLM significantly increased in both groups (CR by 5.5% vs. PL by 3.8%; p < 0.01). The percent changes in PFT after supplementation in R4 (p < 0.001) and R6 (p < 0.03) were significantly different between groups. There was a significant percent increase measured in the CR group (R4 by 10.4%; p < 0.001; R6 by 16.8%; p < 0.001), whereas significant, but lower growth found in the PL group also took place (R4 by 7.1%; p < 0.001; R6 by 14.7%; p < 0.001) after four weeks of rehabilitation. Significantly faster decrease were found in NRS of CR versus PL group during treatment (p < 0.02). We detected significantly lower CK levels increase at the CR group compared to the PL group. The results of this study indicate that Cr supplementation combined with therapeutic strategy effectively supports the rehabilitation of tendon overuse injury of adolescent fin swimmers.